Effects of US Monetary Policy on Eastern European Financial Markets - Viorica Chirila; Ciprian Chirila (CES Working Papers, 2018)
The announcement made by the Fed Chairman, Ben Bernanke, on May 22, 2013 regarding the reduction of the quantitative easing programme that took by storm the financial markets determined the significant volatility increase of the US markets and it was not limited to it. The financial markets in the emerging countries that benefited from an increase in their financial flows during the quantitative easing programme were the most affected by this announcement through the volatility increase, depreciation of exchange rate and massive capital outflows. The current paper tackles volatility and volatility transmission from the US market determined by the change of monetary policy to the Eastern European markets. To study the volatility of each stock and bond market of the countries in Eastern Europe, we used univariate heteroscedastic models while for the analysis of volatility transmission from the US market to the Eastern European markets we used the multivariate heteroscedastic models. The results obtained confirm the volatility transmission both on the stock markets, with the exception of Latvia and Lithuania, and on the bond markets in Eastern Europe.
Keywords: 330; stock market; bond markets; return spillover; volatility spillover; multivariate heteroscedastic model